Respuestas

2012-10-10T05:56:36+02:00

1) 3x=x+6

3x-x=6

2x=6

X=6/2

x=3

3)2(3x+3)-4(5x-3)=x(x-3)-x(x+5)

6x+6-20-12=x^2-3x-x^2+5x

6x-26=2x-6x

-26=2x-6x

-26=-4x

-26/4=x

6.5=x

El 2 no me sale, espero que te sirva

2012-10-10T06:01:28+02:00

El 2 te lo traigo yo:

 

2. 15x-10=6x-(x+2)+(-x+3)

 

Quitando parentesis primero

 

15x-10=6x-x-2-x+3

 

15x-10=4x+1

15x-4x=1+10

11x=11

x=1

 

Y eso es todo.

 

Verificacion:

 

15x-10=6x-(x+2)+(-x+3)

15(1)-10=6(1)-(1+2)+(-1+3)

5=5

 

Saludos.